(untitled) (De la Crítica, 2023)
Discourse is a social practice rooted in human life, both orally and in writing. Its objective is to build texts, linguistic forms that reflect the individual vision of the world in different contexts and the materialization of human thought through the word. The use of language as a communicative system offers multiple options such as phonic, morphosyntactic, lexical and graphic elements, which constitute the speech system for discursive interaction. The discourse is characterized by its complexity and heterogeneity, emphasizing the intentionality of each individual when communicating, that is, the purpose they have when issuing their message, which plays a fundamental role in human daily life. The methodology used in this review has been of a documentary nature based on the positions of Calsamiglia and Tusón (2002), who propose a study on the daily perspective on the discursive nature of the words used to communicate each individual. In other words, discourse analysis allows us to understand how meaning is constructed, the world is represented, and social identities are created in different communicative contexts. Therefore, the individuality of thought will be the enriching factor of a speech, considering it an exhibition on the reality of the speaker and thus expressing an opinion that is anchored to the heterogeneity of ideas that it seeks to communicate.